The Use of ICT-Based Education System in Nepal - Tripathi, Yashodham (A Bi-annual South Asian Journal of Research & Innovation, 2024)
The government of Nepal, recognizing the importance of ICT in achieving quality education, has embarked on various initiatives aimed at transforming traditional educational practices. With the launch of projects like the Nepal Digital Education Framework, the expansion of internet infrastructure, and the introduction of e-learning platforms, ICT in education has begun to take root. However, the journey is not without its challenges. While urban areas are progressively adopting digital tools in classrooms, rural parts of the nation continue to struggle with limited access to technology and internet connectivity.